Development of Class VI Elementary School Thematic Teaching Materials Based Local Wisdom - Wulandari, Retno; Utaminingsih, Sri; Kanzunnudin, Mohammad (Universitas Pendidikan Ganesha, 2020)
There are no teaching materials used by teachers that can foster moral values in students, so it is necessary to have learning materials that introduce the culture or local wisdom of each region. The purpose of this study was to determine feasibility of thematic teaching materials for elementary school class VI theme 1 based on local wisdom. This research method referred to the theory of Borg and Gall, using seven steps or research implementation, namely potentials and problems, research planning, developing initial product, field testing, revision, validation, and final improvement. The data collection techniques used were observation, interview, and questionnaire techniques. The analysis used in this research is quantitative and qualitative analysis including learning observation and validation of teaching material products. Sources of data in this study were grade VI students and teachers. From the material expert validation process obtained an average result of 3,41 with percentage of 85% and very good category. The validation from linguists obtained 90% result with an average 3,6 and very good category. For the result of teacher responses obtained an average result of 3,85 total score 3466 with very good category. For the result of the response students, the average result was 3,94 and the total score was 568 in the very good category. Based on the result of the validation and reinforced by the result of the responses of student and teachers, the thematic teaching materials based on local wisdom of Rembang were declared suitable for use in the learning process.